Mengembangkan Kematangan Spiritual: Peran PAK Dalam Pembentukan Kepribadian Holistik - Fatieli Halawa; Sandra R. Tapilaha (International Forum of Researchers and Lecturers, 2024)
Christian religious education plays an important role in the development of complete personality and spiritual maturity in future generations. This article examines the role of Christian religious education in developing spritual maturity and a complete personaltiy. By using literary analysis anad a philosophical approach, this artikel highlights the importance of Christian religious education in helping people understand their identity and life goals in the broader context of existence. Christian religious education strategies that encourage personal reflection, spritual experience and the application of moral values in daily life are seen as efforts to develop strong and resilient personalities. Thus, this article provides an overview of how Christian religious education can become a pillar in developing the spiritual maturity and integrity of future generations.